Formulation of chitosam-coated N-Acetylcysteine-Loaded nanostructured lipid carrier (CH-NAC-NLC) coating for urinary catheters - Buerano, Vincent Arnel; Delfin, Emanuel John D.; Rivera, Nicola Christine
One of the mechanisms of pathogenesis of CAUTIs is through biofilm formation on urinary catheter surfaces which renders bacteria resistant to the immune system and several antimicrobial agents (Trautner & Darouiche, 2004). To address this, we conducted a study aimed to formulate CH-NAC-NLC coating for urinary catheters which can potentially prevent biofilm formation and subsequently, CAUTIs. CH-NAC-NLCs were prepared through emulsification and ultrasonication method using cetyl palmitate as solid lipid, oleic acid as liquid lipid, and Tween 80 as surfactant; and were coated onto catheters through slurry-dipping technique. CH-NAC-NLCs and CH-NAC-NLC-coated urinary catheters were then characterized and evaluated. The CH-NAC-NLCs were spherical in shape, with average particle size of 187.2 am, polydispersity index of 0.342, and zeta potential of +34.215 m V. Entrapment efficiency and drug loading capacity were found to be 70.8507% and 11,8084%, respectively. The CH-NAC-NICs have a biphasic release profile with 30.39% burst release followed by sustained release until 67.12% over 146 hours. It conformed with Korsmeyer-Peppas kinetics with a Quasi-Fickian diffusion release mechanism. For CH-NAC-NIC-coated urinary catheters, the release profile fitted the Hixson-Crowell model with a triphasie release profile. It followed a 41.81% burst release, followed by a decrease to 8.72% within 2.2 hours and lastly, a sustained release until 73.66% over 145 hours, Overall, we have demonstrated the use of CH-NAC-NLCs as a potential nanopharmaceutical drug delivery system and as catheter coating to prevent biofilm formation, and warrants further study to optimize the formulation.